Effects of Cenococcum Geophilum on the Growth of Seedlings Of Ostryopsis Davidiana Dence. And Pinus Tabuleaformis Carr. (Bangladesh Journal of Botany, 2021)
The affinity and promoting ability of the Cenococcum geophilum strains (CgSO1, CgSB2, CgO5, SPOP2 and Cg5 #) to Ostryopsis davidiana and Pinus tabulaeformis were studied. The results showed that the tested strains formed ectomycorrhizae（ECM）with O. davidiana except the Cg5 # strain and the infection rates were 40-50%. CgSO1 and CgSPOP2 formed ECM with P. tabulaeformis and the infection rates were 10.3 and 12.4%, respectively. C. geophilum can promote the growth of the two host plant seedlings, especially for root growth. Results proved that the affinity of different strains to host plants and the affinity of the same strain to different host plants are different.Bangladesh J. Bot. 50(3): 679-683, 2021 (September)